De hedendaagse erfenis van tien jaar onteigeningen en uitzettingen in de Brusselse Noordwijk (1965‑1975) - Albert Martens (Brussels Studies, 2009)
At the end of the 1960s, the urban area of Brussels underwent a modernisation process which deeply transformed certain neighbourhoods. Ten years earlier, Expo 58, the North-South junction and the construction of the state administrative district had already brought modernist architecture to Brussels. The enthusiasm generated by these projects, the very weak reactions on behalf of those who were affected and the strong growth of the Golden Sixties (1960‑1970) kindled a will among certain local politicians, town planners and architects to pursue the large-scale modernisation of the city. Due to the promise of a significant increase in wealth, a coalition of interests was established with money lenders and the destruction of entire neighbourhoods was organised. This led to the appearance of the urban struggles in Brussels such as those in the Marolle and the North Quarter. The former was a victory and allowed the neighbourhood to be saved. The latter, however, was not able to prevent the destruction of 53 ha of urban fabric and the eviction of more than 3 000 families. A comparative analysis of these two events allows a better understanding of the multiple stakes, the strategies of urban stakeholders and the effects of these struggles on the emergence of a new urban and civic “conscience”.